2018
DOI: 10.1111/iej.13028
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of complementary irrigation routines in debriding pulp tissue from root canals instrumented with a single reciprocating file

Abstract: Aim To compare histologically the debridement efficacy of four irrigation techniques in root canals instrumented with a reciprocating single file. Methodology From recently extracted premolars with vital pulp, 68 were selected and classified as having round canals (mesiodistal diameter similar to buccolingual) or oval‐shaped canals (mesiodistal diameter 2.5 times larger than buccolingual) (n = 32, each) by means of bidirectional radiographs. Four additional uninstrumented samples served as histological control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…, Varela et al . ). Indeed, while the fixed pulp tissue may not retain properties similar to unaffected pulp tissue, this is presently the only reliable method to investigate root canal debridement at the histological level.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…, Varela et al . ). Indeed, while the fixed pulp tissue may not retain properties similar to unaffected pulp tissue, this is presently the only reliable method to investigate root canal debridement at the histological level.…”
Section: Discussionmentioning
confidence: 97%
“…The results agree with a histological study (Varela et al . ), which concluded that ultrasonically activated irrigation resulted in significantly less RPT than syringe irrigation, sonic activation and manual dynamic agitation, when canals were prepared using a Reciproc R25 instrument (VDW GmBH, Munich, Germany). The present study is different from that study as the R25 is a variable tapered instrument, with an apical taper of .08, while the current study used a .04 constant‐tapered instrument.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations